On the age of stratospheric air and ozone depletion potentials in polar regions - Pollock, W. H.; Heidt, L. E.; Lueb, R. A.; Vedder, J. F.; Mills, M. J.; Solomon, S. (1992)
Observations of the nearly inert, man-made chlorofluorocarbon CFC-115 obtained during January 1989 are used to infer the age of air in the lower stratosphere. These observations together with estimated release rates suggest an average age of high-latitude air at pressure altitudes near 17-21 km of about 3 to 5 yr. This information is used together with direct measurements of HCFC-22, HCFC-142b, CH3Br, H-1301, H-1211, and H-2402 to examine the fractional dissociation of these species within the Arctic polar lower stratosphere compared to that of CFC-11 and hence to estimate their local ozone depletion potentials in this region. It is shown that these HCFCs are much less efficiently dissociated within the stratosphere than CFC-11, lowering their ozone depletion potentials to only about 30-40 percent of their chlorine loading potentials. In contrast, the observations of CH3Br and the Halons considered confirm that they are rapidly dissociated within the stratosphere, with important implications for their ozone depletion potentials.